Using Language Games to Enhance EFL Studentsâ€™ Speaking Skill in Indonesia - Marzuki, Abdul Gafur; Kuliahana, Ana (Institut Agama Islam Negeri Imam Bonjol Padang, 2021)
This research aims at enhancing EFL studentsâ€™ speaking skill through the use of language games. The research was designed in the form of Classroom Action Research. It was conducted in two cycles and six meetings. Each cycle consisted of plan, implementation, observation, and Reflection. The researchers employed an observation checklist, field notes, questionnaire, and test to collect the data. The main criterion of success of this research was that the studentsâ€™ scores on the speaking test should achieve a score of 70, and it must be achieved by 75% of the total number of students. The second criterion was that the lecturerâ€™s classroom performance should meet the â€œSuccessâ€ category. The results of the first speaking test showed that from 24 students in the classroom, 15 students got scores of 70 or higher. It was equal to 62.5 %. In cycle 2, the total number of students who got scores of 70 or higher was 21. It was equal to 87.5 %. The result of this research indicated that the use of language games can develop the studentsâ€™ speaking skills